Найди производную функции y=x^2/(x-1) в точке x0=3

nector nector    3   05.06.2019 21:10    1

Ответы
Ульянатв Ульянатв  06.07.2020 08:41
(\frac{x^2}{x-1})' =(x^2(x-1)^{-1})'=(x^2)'((x-1)^{-1})+x^2((x-1)^{-1})'= \\ 
=2x((x-1)^{-1})-x^2(x-1)^{-2}= \frac{2x}{x-1} - \frac{x^2}{(x-1)^2} = \\ 
=\frac{2x(x-1)-x^2}{(x-1)^2}=\frac{2x^2-2x-x^2}{(x-1)^2}=\frac{x^2-2x}{(x-1)^2}=\frac{x(x-2)}{(x-1)^2}

Считаем значение производной в х₀:
\frac{3(3-2)}{(3-1)^2}= \frac{3}{2^2} = \frac{3}{4}
ответ: 0,75
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра